2020
DOI: 10.32607/actanaturae.11154
|View full text |Cite
|
Sign up to set email alerts
|

The Molecular and Cellular Mechanisms Associated with a Microvascular Inflammation in the Pathogenesis of Heart Failure with Preserved Ejection Fraction

Abstract: Heart failure withpreserved ejection fraction (HFpEF) is a severe disease with an often unfavorable outcome. The prevalence of HFpEF continues to increase, while effective treatment options remain elusive. All the medical strategies used toimprove the outcome in a heart failure with reduced ejection fraction proved ineffective in HFpEF, which was probably due to the different mechanisms ofdevelopment of these two types of heart failure and the diversity of the HFpEF phenotypes. According to the current paradig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0
4

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(14 citation statements)
references
References 74 publications
0
10
0
4
Order By: Relevance
“…M1 macrophages secrete pro-inflammatory cytokines TNF and IL-1β, which maintain the inflammatory response and myocardial injury; M2 macrophages are involved in fibrosis and diastolic dysfunction by producing pro-fibrotic cytokines TGF-β, IL-10, galectin-3, and osteopontin [ 29 ]. The two macrophage phenotypes are often present together during chronic coronary microvascular inflammation [ 6 ]. The synergy of M1 (pro-inflammatory phenotype) and M2 (pro-remodeling/anti-inflammatory phenotype) aggravates the feedforward loop of myocardial inflammation and fibrosis.…”
Section: The Comorbidity–inflammation Paradigm In Hfpef Is Closely Re...mentioning
confidence: 99%
See 1 more Smart Citation
“…M1 macrophages secrete pro-inflammatory cytokines TNF and IL-1β, which maintain the inflammatory response and myocardial injury; M2 macrophages are involved in fibrosis and diastolic dysfunction by producing pro-fibrotic cytokines TGF-β, IL-10, galectin-3, and osteopontin [ 29 ]. The two macrophage phenotypes are often present together during chronic coronary microvascular inflammation [ 6 ]. The synergy of M1 (pro-inflammatory phenotype) and M2 (pro-remodeling/anti-inflammatory phenotype) aggravates the feedforward loop of myocardial inflammation and fibrosis.…”
Section: The Comorbidity–inflammation Paradigm In Hfpef Is Closely Re...mentioning
confidence: 99%
“…Increased levels of ROS frequently attack the cellular genome, proteins, and lipids, leading to a rise in lipid peroxidation (LPO) products, disruption of endogenous antioxidant mechanisms, and a decrease in glutathione (GSH) levels [ 5 ]. Furthermore, this systemic pro-inflammatory state can affect coronary microvascular function and compromise cardiomyocyte structure and cardiac function [ 6 ], implying a connection between inflammation, oxidative stress of ferroptosis, and HFpEF. In addition, studies have shown that left ventricular (LV) diastolic function may be a more sensitive early marker of myocardial iron overload than systolic function [ 7 , 8 ].…”
Section: Introductionmentioning
confidence: 99%
“…Об этом же говорят и результаты нашего ретроспективного когортного исследования, в котором при длительном наблюдении за 223 пациентами с бессимптомным ГС (медиана наблюдения составила 8,1 года) систолическая дисфункция ЛЖ по "внутреннему" механизму возникла лишь у 7% пациентов, причём во всех случаях была незначительной [22]. нического воспаления коронарных микрососудов [27]. В экспериментальных моделях с перегрузкой давлением в гипертрофированном миокарде помимо фиброза всегда обнаруживаются и признаки воспаления, при этом области фиброза и воспаления полностью совпадают, воспаление случается раньше фиброза, и если удаётся подавить воспаление, то не будет и фиброза [28].…”
Section: при гс сннфв возникает крайне редкоunclassified
“…Откуда в гипертрофированном миокарде берётся воспаление? Большинство больных с ГЛЖ и СНсФВ имеют сопутствующие заболевания, такие как ожирение, сахарный диабет типа 2, хроническую болезнь почек, хроническую обструктивную болезнь лёгких, анемию [27]. Эти заболевания поддерживают в организме хронический провоспалительный статус, который проявляется высоким уровнем циркулирующих провоспалительных цитокинов.…”
Section: при гс сннфв возникает крайне редкоunclassified
“…Myocardial microvascular inflammation, mediated by pro-inflammatory cytokines, leads to activation of endothelial cells, which highly express adhesion molecules that trigger monocyte migration from the bloodstream into the myocardium and their differentiation into macrophages. This vicious circle leads to a state called “endothelial dysfunction”, which contributes to fibrosis and progressive diastolic dysfunction [ 7 , 8 ]. Conversely, HF with reduced ejection fraction (HFrEF; LVEF ≤ 40%) is mainly characterized by systolic dysfunction as a consequence of a direct heart damage, such as an acute coronary syndrome, a cardiomyopathy or a valve disease.…”
Section: Introductionmentioning
confidence: 99%